1988
DOI: 10.1088/0951-7715/1/2/003
|View full text |Cite
|
Sign up to set email alerts
|

Hopf bifurcation with the symmetry of the square

Abstract: Four identical nonlinear oscillators, coupled with the symmetry of a square, can undergo o symmetric version of the standard Hopf bifurcation. Golubitsky and Stewart have studied the case of N oscillators coupled in a ring with nearest-neighbour coupling. Their results are incomplete for the square case ( N = 4) because they only considered periodic solutions which have 'maximal' symmetry. Here we study the dyncjmics of all possible square-symmetric Hopf bifurcations; these codimension-one bifurcations are par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 6 publications
4
119
0
Order By: Relevance
“…Equations (18a,b) are identical to the equations describing a Hopf bifurcation with D4 symmetry considered by Swift [27] in the context of coupled oscillators. However, since our primary interest is in the large but finite L case (for particular scaling regimes), we are led to consider symmetry-breaking unfoldings of this limiting D4-symmetric case.…”
Section: Reduction To a Finite-dimensional Systemmentioning
confidence: 95%
See 2 more Smart Citations
“…Equations (18a,b) are identical to the equations describing a Hopf bifurcation with D4 symmetry considered by Swift [27] in the context of coupled oscillators. However, since our primary interest is in the large but finite L case (for particular scaling regimes), we are led to consider symmetry-breaking unfoldings of this limiting D4-symmetric case.…”
Section: Reduction To a Finite-dimensional Systemmentioning
confidence: 95%
“…Consequently the behavior of each mode on the "fast" time scale is dominated by its oscillation frequency, Le., zl rv eiLl.w t, z2 rv e -iC.w t; cf. (27). Looking now at the nonlinear terms in (24a,b) it is clear that the final term in each fluctuates rapidly compared to the first two terms and hence effectively "averages out" to zero.…”
Section: B Asyldptotic Scaling: T:1jr" I/l2 T:1jw '" I/lmentioning
confidence: 95%
See 1 more Smart Citation
“…Note that the case n = 4 and so m − 2 = 0 is special. The existence of branches of periodic solutions of (4.12) with submaximal symmetry that bifurcate from (0, 0) in a generic Hopf bifurcation with D 4 -symmetry is proved by Swift [8].…”
Section: Generic Hopf Bifurcation With D N -Symmetrymentioning
confidence: 99%
“…In this note we prove in Theorem 4.2 that if we assume (1.1) satisfying the conditions of the Equivariant Hopf Theorem and f is in Birkhoff normal form then, when n = 4 and n ≥ 3, the only branches of smallamplitude periodic solutions of period near 2π of (1.1) that bifurcate generically from the trivial equilibrium are the branches of solutions guaranteed by the Equivariant Hopf Theorem. The case when n = 4 differs markedly from those other n. Swift [8] studies the dynamics of all possible square-symmetric codimension one Hopf bifurcations. In particular, it is shown that periodic solutions with submaximal symmetry bifurcate from the origin for open regions of the parameter space of the cubic coefficients in the Birkhoff normal form.…”
Section: Introductionmentioning
confidence: 99%